Stochastic analysis of flow-induced dynamic instabilities of wind turbine blades. Issue 137 (February 2015) - Pourazarm, Pariya; Caracoglia, Luca; Lackner, Matthew; Modarres-Sadeghi, Yahya
Abstract: Wind turbine blades continue to grow in length to extract more energy from the wind. This trend results in more flexible blades that are more susceptible to flow-induced instabilities. Recent studies have shown that coupled-mode flutter can be a major concern for future wind turbine blades. In this work, we study the influence of uncertainty in system parameters on the onset of coupled-mode flutter for wind turbine blades. We consider two major sources of randomness: (i) flow forces through a random lift coefficient and (ii) structural properties through a random variation of the blade׳s torsional natural frequency. We use a linear stability analysis in order to predict the onset of instability and we apply the method to the NREL 5 MW wind turbine blade. Both normal and uniform probability distributions are considered to describe the random parameters. For each case, the coefficient of variation ( cov ) is set to be equal to 0.1 and 0.2, which has been shown in the literature to be a plausible variability. We show that randomness in both the flow forces and the structural properties affect the onset of instability. In all the cases, the higher cov values result in non-negligible occurrence of instability at a blade critical rotor speed considerably lower than the value found in the absence of randomness. It is also found that the structural randomness can decrease the critical speed for the onset of coupled-mode flutter to speeds lower than the wind turbine׳s designed operational speed.